Ion mobility mass spectrometry of two tetrameric membrane protein complexes reveals compact structures and differences in stability and packing. - Wang, S; Politis, A; Di Bartolo, N; Bavro, V; Tucker, S; Booth, P; Barrera, N; Robinson, C (2010)
Here we examined the gas-phase structures of two tetrameric membrane protein complexes by ion mobility mass spectrometry. The collision cross sections measured for the ion channel are in accord with a compact configuration of subunits, suggesting that the native-like structure can be preserved under the harsh activation conditions required to release it from the detergent micelle into the gas phase. We also found that the quaternary structure of the transporter, which has fewer transmembrane subunits than the ion channel, is less stable once stripped of detergents and bulk water. These results highlight the potential of ion mobility mass spectrometry for characterizing the overall topologies of membrane protein complexes and the structural changes associated with nucleotide, lipid, and drug binding.